Nature-Based Experiences in Urban Preschool Environment: A Systematic Contextual Mapping Study - Isa, Farhana Mohammed; Grierson, David (MAJ - Malaysia Architectural Journal, 2025)
Children’s connection with and exposure to the natural environment is a vital part of their growth and development process, having been shown to support their learning opportunities and improve their overall health and well-being, particularly during the first five years of life. Increasingly environmental issues such as climate change, the scarcity of green spaces due to urbanisation, post-pandemic health and safety concerns, and the emergence of technology-driven indoor classroom learning present complex challenges that restrict urban preschooler’s participation in nature-based learning play and result in a lack of access to nature. Although recent progress has been made within teaching pedagogy around outdoor learning and nature-based play, discussions on the role of architecture in supporting improvement and diverse interactions with nature and in utilising green spaces in preschool environments still need to be included. Derived from a systematic literature review, this paper offers a framework for contextual mapping that can be used to evaluate architecture-nature provision in preschools across two continents. In this study, child-nature-architecture assessment tools are highlighted to demonstrate the potential of architecture to contribute positively to preschool children’s experiences of nature, enhance their learning opportunities, and improve their overall health and well-being. The work aims to provide insights into nature-based experiences in preschool environments and to identify the similarities and differences of nature-based experience concepts and approaches within preschool environments across two continents to find useful common ground. The systematic contextual mapping study should enable stakeholders, including architects and educationalists, alongside governing bodies, to better consider the provision of access to nature in preschool architecture through design interventions in existing facilities, to inform proposals for the design of new preschools, and to improve investment decision-making for future education facilities.